APLIKASI SPELLING CORRECTING PADA PENULISAN BAHASA INDONESIA DENGAN METODE JARO WINKLER - Samudero, Fauzan Risang Agung; Jati Sasongko Wibowo (Elkom: Jurnal Elektronika dan Komputer, 2024)
Typing errors in documents are fairly common. The process of checking typing errors manually will take a lot of time. Therefore, a system called Indonesian spelling correcting with Jaro Winkler is needed. Spelling Correcting is a feature that can check and correct word writing errors automatically. Jaro Winkler is an algorithm used for the word correction process by calculating the value obtained from the results of the operation of modifying one word with another word with the help of a matrix. Based on the results of trials on 13 words, namely "Alaman Amus Seperti Pada Gamba Tersebut Digunakan Untuk Memasukkan Data Kata Pada KBBI ", this spelling correcting application can produce 3 correct word corrections to " halaman kamus seperti pada gambar tersebut digunakan untuk data pada kbbi ", each Word improvement is calculated using the Jaro Winkler formula, getting a score above 0.94 for each word tested.